PENGARUH LOKASI DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI KEDAI KIMMI NOODLE & RICE PANDAAN KABUPATEN PASURUAN - Juniar Ekywati; Eva Mufidah; Dwita Laksmita Rachmawati (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Currently, the food industry is increasingly experiencing development, supported by the existence of micro, small and medium enterprises (MSMEs) established by the community as a source of livelihood. Kimmi Noodle & Rice is a shop that sells contemporary food that is loved by young people. In this research there are problems regarding location and word of mouth. This research aims to determine the influence of location and word of mouth on purchasing decisions at the Kimmi Noodle & Rice Pandaan shop, Pasuruan Regency. This research uses a quantitative method, using a non-probability sampling technique, namely purposive sampling with a sample size of 60 respondents who have made purchases at the Kimmi Noodle & Rice shop within a period of approximately 6 months. The results of this research show that (1) location does not have a significant influence on purchasing decisions with a significance value of 0.161 > 0.05. (2) word of mouth has a significant influence on purchasing decisions with a significance value of 0.000 < 0.05. (3) location and word of mouth simultaneously have a significant effect on purchasing decisions with a significance value of 0.000 < 0.005. (4) location and word of mouth have an influence of 55.8% on purchasing decisions and the remaining 44.2% is influenced by other variables not examined in this research